Islamization Through the Sound Arts (American Journal of Islam and Society, 1986)
I. The NeedJust as philosophical and religious writings are a verbal expression ofthe ideology of a people, just as social and economic institutions are determinedby that basic ideology, so also music and the sound arts are "aanslations"of the deepest convictions of a people. They fit into the cultural wholeas pieces of a giant mosaic, each tessera reflecting the world view of thatpeople and corresponding to the other expressions of that spirit. Fulfillingthis role in the culture, the arts of sound become an important, even crucial,bulwark of a people's heritage.In English, such aesthetic "translations" of the ideology into pitches anddurations are known as "music"; and the term has generally encompassed allforms of sound art, regardless of their intrinsic characteristics or the circumstancesof their performance. In Islamic culture, however, there is no termor expression which includes all types of sound art. The term musiqa, whichis sometimes loosely equated with the English term "music," is certainly inadequate.That Arabic term derived from the Greek has been applied primarilyto those forms which, because of context of performance or aestheticcharacteristics, were culturally and religiously regarded with some degree ofsuspicion, or in certain cases, even condemned. The term miidqii has neverincluded those genres of sound art which were wholeheartedly approved andfostered by the culture, e.g., Qur'anic chant, the adhan, the pilgrimage chants,madih chanted poetry (shi'r). Elsewhere I have therehre advocated the useof a new expression, Handasah al sawt (al Faruqi 1982:30ff). This designationwould cover all the forms of sound art, and thus more truly equate withthe term "music" and its cognates in other European languages. It is with thatexpression and an appreciation of the wide meaning which it implies that thispresentation continues.Handasah al sawt is a cultural phenomemon which can play an important ...